Case of Microcephaly after Congenital Infection with Asian Lineage Zika Virus, Thailand - Thidathip Wongsurawat; Niracha Athipanyasilp; Piroon Jenjaroenpun; Se‐Ran Jun; Bualan Kaewnapan; Trudy M. Wassenaar; Nattawat Leelahakorn; Nasikarn Angkasekwinai; Wannee Kantakamalakul; David W. Ussery; Ruengpung Sutthent; Intawat Nookaew; et al. (2018)
We sequenced the virus genomes from 3 pregnant women in Thailand with Zika virus diagnoses. All had infections with the Asian lineage. The woman infected at gestational week 9, and not those infected at weeks 20 and 24, had a fetus with microcephaly. Asian lineage Zika viruses can cause microcephaly.